Sistem Kontrak dan Serikat Pekerja di Sektor Pariwisata Bali: Respons terhadap Perselisihan dan Advokasi - Komang Trisna Handayani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Tourism in Bali, as the backbone of the regional economy, absorbs more than 50% of the workforce and gives rise to complex labor dynamics. Although Law No. 13 of 2003 on Manpower and Law No. 21 of 2000 on Trade Unions guarantee worker protection and freedom of association, the reality on the ground is still marked by the misuse of fixed-term employment contracts (PKWT), violations of outsourcing regulations, and both structural and cultural barriers to union formation. This article employs a normative juridical approach, using statute, conceptual, and case-based methods to analyze the regulatory framework and the responses of workers, employers, and government actors in addressing industrial relations disputes within Bali’s tourism sector. The findings reveal a significant gap between written legal norms and actual practice: repeated extensions of PKWT, outsourcing of core tasks such animal caretaking, union-busting through dismissal of union members, and weak law enforcement at regional level. Trade unions play a role in mediation and advocacy, but their performance is hindered by employer intimidation, low legal literacy among workers, and limited institutional support. Bridging this gap requires strict oversight, legal education for workers, as well as the strengthening of union capacity and the authority of local governments.